Family Support and Loneliness among Older Persons in Multiethnic Malaysia - Jane Kimm Lii Teh; Nai Peng Tey; Sor Tho Ng (The Scientific World Journal)
This study investigates factors affecting older persons’ state of loneliness in multiethnic Malaysia using data from the 2004 Malaysian Population and Family Survey, the first nationally representative sample in Malaysia. The study sample was extracted to include Malays, Chinese, Indians and other Indigenous groups aged 60 and above, and who had children (n = 1791). Cross tabulations and ordinal logistic regression methods were used in the analysis. Among the ethnic groups, older Malays were more likely than their Chinese and Indian counterparts to experience loneliness. Loneliness was found to be associated with age, marital status, education level, sources of income, health status, and physical limitations. Among older people, feelings of loneliness were inversely related with coresidence with adult children and participation in religious activities. Sociodemographic changes have eroded the traditional family support system for the elderly, while social security remains inadequate. This study shows the important role of family in alleviating loneliness among older people. Hence the need to promote and facilitate coresidence, as well as participation in religious activities, and a healthy lifestyle as a priority strategy is in line with the objectives of the National Policy for the Older People.